The analytic process of Q methodology / Siti Maftuhah Damio - Damio, Siti Maftuhah (Penerbit UiTM (UiTM Press), 2018)
The purpose of this article is to describe the analytic process of a method of data collection known as Q Methodology. This method is an alternative method in collecting data especially suited to research on “points of views” (Coogan & Herrington, 2011, p. 24). The analytic process of Q methodology involves factor analysis, a mathematical technique that reveals underlying explanations for patterns in a large set of data (Webler, Danielson and Tuler, 2007). This is known as Q technique factor analysis which “look for groupings of similar Q-sorts which represent similar viewpoints” (Bradley, 2007). To identify the factors, a statistical program known as Method, a program which has been tailored to meet the requirement of Q Methodology is utilised. This is a free downloadable program which can be accessed from the web. Method Version 2.11 was used to exemplify the process of Q Methodology analysis in this article. The analysis process involves three main stages. The first is data entry where encompasses 6 steps of keying in data. Data exploration is the second stage where a number of factors are produced by looking at patterns from the Q sorts. The final stage is data interpretation of the factors which is guided by the desire to remain true to what the data showed. This paper, however, looks into the first stage of Q analysis process which is data entry.